Monique simplified the expression correctly. The expression can be simplified step by step using the laws of exponents as follows:
(25)2.2(-4)
= (5^2) * (2^2) * (-4)
= 5^(2+2) * (-4)
= 5^4 * (-4)
= 625 * (-4)
= -2500
So the correct simplified expression is -2500, which matches Monique's answer. Allison's simplification was incorrect.
Monique and Allison simplified the same expression but ended up with different answers. Their work is shown below.
Monique's Work: (25)2.2(-4) 210.2(-4)
= 214
Allison's Work:
(25)22(-4) 27.2(-4)
=23
Did either student simplify the expression correctly? If so, tell who and explain how her work follows the laws of exponents. If neither student is correct, simplify the expression and explain how it follows the laws of exponents
1 answer